Molecular Characterization and DNA-sensing using Graphene Electrochemical Devices under Illumination - Alpuim, Pedro; Pinzón, Edgar [UNESP]; Lopes, Laís C. [UNESP]; Domingues, Telma; Borme, Jérôme; Godoy, Erika [UNESP]; Raposo, M. Manuela M.; Bueno, Paulo R. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2023)
In the AC-electrochemical mode, the signal of quantum capacitance (Cq) of individual graphene channels was resolved as a function of a superimposed DC bias potential through electrochemical impedance spectroscopy (EIS). This capacitive response was used to study the electronic states of push-pull molecules immobilized on the graphene surface in the dark and under visible illumination in the 400 to 580 nm range. The same technique will be further used in the molecular detection of target DNA by functionalizing the graphene surface with complementary probe-DNA and monitoring the Cq-minimum (Dirac point) changes for different target-DNA concentrations in the dark and under visible illumination.